Practical Considerations Relative to Mid-Life Career Counselling - Talley, William M. (Canadian Journal of Counselling and Psychotherapy, 2012)
Some of our ideas that have been derived from traditional psychology coursesmay block our thinking when it comes to mid-life career change. More recentdevelopments in adult psychology and current research in adult education aboutcognitive development and learning styles of adults should give us a differentperspective in this area. There are some approaches other than psychological testing,job information, and retraining that may facilitate a career change at mid-life. Thisarticle is an attempt to clarify some of our thinking about learning ability in a-dulthood, role change at various times of Ufe, and attitudinal change. Finally, anumber of probing questions are presented with the intention of helping individualsassess their readiness for changing a career at mid-life.